ULTRASOUND-ASSISTED EXTRACTION SENYAWA ANTIOKSIDAN DARI LIMBAH BIJI PEMBUATAN MINYAK BUAH MERAH (Pandanus conoideus) - Frenly Wehantouw; Risma Situngkir; Elly Suoth (Sam Ratulangi University, 2023)
The aim of this research was to obtain antioxidant active component from Papuan red fruit oil waste using Ultrasound-assisted extraction. The research was done started from the making of Papuan red fruit oil, extraction and bioactive component analysis (total tocopherol and betacaroten) using spectrophotometry. The result shows that waste from Papuan red fruit oil process contains high amount of yield at 20 minutes extraction time with total carotenoid 20, 23 ppm and tocopherol absorbance 1.04. Ultrasound assisted extraction method significantly increase carotenoid content aw well as tocopherol (p<0.05).